A Review of Vasa (Adhatoda Vasica): Therapeutic Benefits and Formulations in Ayurveda - Sabahat Anjum; Shalini Varshney (International Journal of Ayurveda and Pharma Research, 2024)
In today’s world, numerous old and emerging diseases lack adequate management approaches. Ayurveda, an ancient system of medicine, provides fundamental principles for diagnosing, preventing, and treating diseases. The objective of this study was to gather, analyze, and present information on the therapeutic properties and formulations of Vasa. A comprehensive review of classical Ayurvedic texts including Samhitas, Nighantus, and other relevant literature was conducted. Information on the synonyms, properties, actions, and formulations of Vasa was systematically organized. The review highlights therapeutic applications, dosage forms, and modes of administration as per different classical texts. Vasa (Adhatoda vasica) is a highly valued Ayurvedic herb, known for its therapeutic benefits, particularly in the treatment of respiratory disorders. It has been extensively referenced in classical texts for its therapeutic actions such as Kasahara, Shwashara, Shothahara, Hridya, Raktastambhan and Jwaraghna karma. Over 203 internal formulations and 38 external formulations featuring Vasa are documented across classical texts. These formulations help to manage various diseases like Kasa, Shwasa, Kushtha, Vatrakta and Raktapitta. In conclusion, Vasa is a critical Ayurvedic herb with broad applications, especially for respiratory ailments. Classical Ayurvedic texts provide extensive formulations for both internal and external uses, validated by modern pharmacological research particularly for coughs, asthma, fevers, and infections. While modern research has confirmed many of Vasa's pharmacological activities outlined in Ayurveda, further scientific investigation is needed to fully validate its other therapeutic effects.